ANALYSIS OF THE EFFECT OF COAL QUALITY ON THE ELECTRICITY GENERATING COST AT A SUSUSTEAM POWER PLANT - Dandi Pratama; Solly Aryza Lubis; Hamdani Hamdani (INFOKUM, 2022)
Coal is one of the most extensively used energy sources in power plants. The analysis conducted on the Susu Steam Power Plant Unit 2 in 2021 showed that the lower the calorific value of the coal used, the greater the mass flow rate of coal, while the mass flow rate of steam is relatively the same. The higher the load, the higher the coal mass flow rate, the lower the specific fuel consumption (kg/kWh), and the lower the heat rate. Additionally, the thermal efficiency increases. If a load of 70 MW to 100MW is employed, it will save more on coal usage with a composition of 100% LRC. At a load of 100to 180MW, it is more efficient to use coal with a composition of 25% MRC and 75% LRC. From the average value of the production cost, the use of coal with 100% LRC composition is more efficient, but it cannot achieve the highest load with this composition. When examined from the average value, the one that can meet the largest load and is more efficient is employing a coal composition of 25% MRC and 75% LRC